A Descriptive and Contrastive Study of English and Arabic Vowels: A Selective Study - . Abdulkareem Fadhal Mohammed (Taez University, 2023)
This study highlights an important issue; the contrastive analysis of English and Arabic Vowels. The current study aims to compare English and Arabic Vowels to enable the students to understand the similarities and differences between the English and Arabic segmental vowel phonemes. The study deals on one hand on the difficulties that a learner faces in pronouncing English words with vowel sound as there is no correspondent vowel in Arabic language. On the other hand, it investigates the common errors that are committed by students while pronouncing the vowel sounds according to their spelling form to predict pronunciation problems to avoid them and find out practical measures and solutions to make sure that they will not occur. Thus, the students can learn English vowels and avoid committing errors in the mirror of their understanding of their differences form Arabic vowel sounds. This study is also concerned with developing solutions and suggestions to solve the problems that learners face while pronouncing words that contain vowels. This is a case study in which the descriptive method is used and thirty male and female students from the Department of English Language, College of Education, Saber, University of Aden are randomly selected as the sample. The learner's speeches during talks, lectures and presentations in the class are recorded to collect the data as naturally as possible. The comparative and contrastive methods are also applied in order to find out the similarities and differences between English and Arabic vowel sounds. The data is analyzed to obtain the results about different English vowels from the Arabic vowel sounds.